Aerodynamic admittance of truss girder in homogenous turbulence. Issue 172 (January 2018) - Zhong, Yingzi; Li, Mingshui; Ma, Cunming
Abstract: An approach to directly identify truss girder's aerodynamic lift admittance by buffeting force measurement is put forward. Based on an assumption that a truss girder is equivalent to a continuous cross-section girder, three forms of aerodynamic lift admittance are deduced: complete 2-dimensional, 3-dimensional and 2-wavenumber. Span-wise lift coherence and correlation functions of the equivalent truss cross-section are derived as well. A large-span truss girder bridge is adopted as prototype to validate the approach. Numerical solutions of above-mentioned items are obtained through wind tunnel tests. The configuration of truss girder lift admittance is proved different from traditional known admittance feature. Energy transferring tendency is revealed by 2-wavenumber admittance. Complete 2-dimensional lift admittance is found possible to overestimate truss girder's buffeting response at the most concerned wavenumber range. Span-wise lift correlation and coherence of the equivalent cross-section are proved slightly lower than that of truss segment. In addition, a brief study on influence of slight varied incident angle is carried out, in which aerodynamic lift span-wise coherence is proved obviously affected at low wavenumber range. Graphical abstract: 2-wavenumber lift admittance of equivalent truss cross-section reveals energy transferring trend of this structure: gathering turbulence energy mainly to a relative low wavenumber scope. 2-dimensional admittance is larger than 3-dimensional admittance at reduced frequency range from 0.03∼0.6, which might cause imprecise buffeting response calculation. 3-dimensional segmental admittance is in parallel lower that cross-sectional admittance, most possibly due to aerodynamic force redistribution on truss segment. Span-wise coherence and correlation coefficient of equivalent cross-section are obtained and observed a little smaller than that of segment, which is reasonable, for truss girder has already "averaged" cross-sectional correlation. The result proved buffeting force's correlation is larger than turbulence's once again. (a) 2-wavenumber lift admittance of equivalent cross-section. (b) Comparison of 3 dimensional segmental admittance, 2-dimensional and 3-dimensional cross-sectional admittance and Sears function. (c) Span-wise coherence of equivalent cross-section under different intervals. (d) Span-wise correlation of equivalent cross-section and its comparison with segmental and turbulence correlation. Highlights: This method is applicable for segments of arbitrary span length with any cross-section form in wind tunnel tests. Aerodynamic admittance of a truss girder segment is given out in 2-wavenumber and 3-dimensional form. Three forms of equivalent cross-sectional admittance are given out: 2-wavenumber, 3-dimensional and 2-dimensional. Span-wise coherence and correlation function of equivalent truss cross-section is given out. The influence of incident angle is briefly discussed.